Teaching peritoneal dialysis in Australia: An opportunity for improvement. Issue 3 (20th February 2018) - Boudville, Neil; Cho, Yeoungjee; Equinox, Keri‐Lu; Figueiredo, Ana Elizabeth; Hawley, Carmel M; Howard, Kirsten; Johnson, David W; Jose, Matthew; Lee, Anna; Maley, Moira Alison; Moodie, Jo‐Anne; Pascoe, Elaine M; et al.
Abstract: Introduction: Up to a 10‐fold difference in clinical outcomes between Australian peritoneal dialysis (PD) units exists. There is an international focus on the harmonization of educational practices in PD to determine whether this may lead to improved patient outcomes. Aims: The aim of this paper is to evaluate the current teaching practices of nurses and patients in Australian PD units. Methods: An online survey with questions on nurse and patient training was made available to PD units in Australia. Results: Thirty‐eight (70%) of 54 PD units in Australia completed the survey. A written standardized curricula was utilized in 21 units (55%) for nursing staff and 30 units (79%) for patients, with 23% and 12% including an electronic delivery component for each group, respectively. Universal teaching of adult learning principles was not demonstrated. The hours spent on teaching nursing staff ranged from <15 h in 24% to >100 h in 21% of units. The average number of hours spent by nurses each day to train patients ranged from <2 h in 14% to >6 h in 11% of units, with the average total training days ranging from 2 to 3 days in 14% to over 7 days in 14% of units. Staff and patient competency assessments were performed routinely in 37% and 74% of units, respectively. Conclusions: Considerable differences exist amongst Australian PD units in the education of staff and patients. There is a general lack of delivery and competency assessment to meet educational standards. It remains to be seen if harmonization of educational curricula can translate to improved clinical outcomes. Summary at a Glance: This is a qualitative study on the training methodology of patients and medical staff on peritoneal dialysis in Australian PD units. This study demonstrates significant differences in training curricula of the various units.